THE INFLUENCE OF FINANCIAL LITERACY, DEMOGRAPHIC FACTORS, LOCUS OF CONTROL AND PARENTAL INCOME ON BEHAVIOR STUDENT FINANCE (Study on Management Study Program Students at Bumi Persada University) - Zuraida; Muhammad Multazam; Yusnidar; Ayu Anora; Maisyuri (CV. Radja Publika, 2024)
This study aims to determine the effect of financial literacy, demographic factors, locus of control, parental income on financial behavior in UNBP Management Study Program Students. The data used in this study are primary data with a sample of 115 students and distributed online using a questionnaire obtained from the main source, namely UNBP Management Study Program Students. The data analysis method uses multiple linear regression analysis. The results of this study partially indicate that the financial literacy variable has a positive and significant effect on the financial behavior of UNBP Management Study Program students, the demographic factor variable has a positive and significant effect on the financial behavior of UNBP Management Study Program students, the locus of control variable does not have a significant effect on the financial behavior of UNBP Management Study Program students, and the parental income variable has a positive and significant effect on the financial behavior of UNBP Management Study Program students.